NSs filament formation is important but not sufficient for RVFV virulence in vivo - Li, Shufen; Lozach, Pierre-Yves (Viruses, 2019)
Rift Valley fever virus (RVFV) is a mosquito-borne phlebovirus that represents as a serious health threat to both domestic animals and humans. The viral protein NSs is the key virulence factor of RVFV, and has been proposed that NSs nuclear filament formation is critical for its virulence. However, the detailed mechanisms are currently unclear. Here, we generated a T7 RNA polymerase-driven RVFV reverse genetics system based on a strain imported into China (BJ01). Several NSs mutations (T1, T3 and T4) were introduced into the system for investigating the correlation between NSs filament formation and virulence in vivo. The NSs T1 mutant showed distinct NSs filament in the nuclei of infected cells, the T3 mutant diffusively localized in the cytoplasm and the T4 mutant showed fragmented nuclear filament formation. Infection of BALB/c mice with these NSs mutant viruses revealed that the in vivo virulence was severely compromised for all three NSs mutants, including the T1 mutant. This suggests that NSs filament formation is not directly correlated with RVFV virulence in vivo. Results from this study not only shed new light on the virulence mechanism of RVFV NSs but also provided tools for future in-depth investigations of RVFV pathogenesis and anti-RVFV drug screening.
Gesehen am 31.10.2019